Keratinoctye-neuro-immune-units (KNICUs): collaborative impact on the initiation and maintenance of psoriasis - Chen, Xue-Yan; Wang, Zhao-Yuan; Zhou, Yuan; Ye, Li-Ran; Man, Xiao-Yong (Frontiers in Medicine, 2023)
Skin is the outmost barrier that separates the human body from the external environment. In psoriasis, immune cells are resident and / or infiltrated into the epidermis in order to form the epidermal (epithelial) immunological microenvironment (EIME) and constitute a complex interaction with keratinocytes, together with nerve and microbiota influence. The proposed hypothesis is that psoriasis is a chronic inflammatory disease mainly mediated by specific inflammatory environment composed by keratinocyte-neuro-immune cell units (KNICUs), which is the interaction of activated epidermal immune cells, keratinocytes, peripheral nerves and skin microbiota. Multiple units gathering to complete circulatory and amplified loop, consequently serve as group army in the initiation and maintenance of psoriasis.